2018
DOI: 10.1038/s41467-018-07853-z
|View full text |Cite
|
Sign up to set email alerts
|

Ezh2 programs TFH differentiation by integrating phosphorylation-dependent activation of Bcl6 and polycomb-dependent repression of p19Arf

Abstract: Ezh2 is an histone methyltransferase (HMT) that catalyzes H3K27me3 and functions in TH1, TH2, and Treg cells primarily via HMT activity. Here we show that Ezh2 ablation impairs T follicular helper (TFH) cell differentiation and activation of the TFH transcription program. In TFH cells, most Ezh2-occupied genomic sites, including the Bcl6 promoter, are associated with H3K27ac rather than H3K27me3. Mechanistically, Ezh2 is recruited by Tcf1 to directly activate Bcl6 transcription, with this function requiring Ez… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 77 publications
7
61
0
Order By: Relevance
“…However, in lymphocytes, FOXO1 also regulates expression of genes important for lymphocyte development, activation, and migration. AKT also influences the activity of multiple other transcriptional regulators in lymphocytes, including NF‐kB (via phosphorylation of CARMA), the transcription factor BACH2, and the methyl‐transferase EZH2 …”
Section: Signaling Pathways Downstream Of Pi3kmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in lymphocytes, FOXO1 also regulates expression of genes important for lymphocyte development, activation, and migration. AKT also influences the activity of multiple other transcriptional regulators in lymphocytes, including NF‐kB (via phosphorylation of CARMA), the transcription factor BACH2, and the methyl‐transferase EZH2 …”
Section: Signaling Pathways Downstream Of Pi3kmentioning
confidence: 99%
“…Nonetheless, cross‐talk between PI3K and TCF‐1 is complex, affecting both positive regulation of TCF‐1 via FOXO1, and negative regulation via inhibition of GSK3‐mediated repression of β‐catenin, a coactivator of TCF‐1, leading to potential increases in TCF‐1 activity . A recent paper has shown that EZH2 binds TCF‐1, thereby promoting Tfh‐cell generation; this activity of EZH2 required phosphorylation on S21, the AKT phosphorylation site …”
Section: Pi3k Signaling Pathways Orchestrating T Follicular Helper Cellsmentioning
confidence: 99%
“…Studies in recent years highlight a crucial role of EZH2 functioning as an epigenetic repressor via the catalyzing of H3K27 tri-methylation in T cell activation [4], differentiation [4], plasticity, and lineage commitment [5,6] by safeguarding correct downstream gene expressions. The repressive targets include key transcriptional factors which function as pivotal regulators of differentiation or self-tolerance [7][8][9], cytokines like interleukins, and IFN-γ [7,[10][11][12] as well as cell cycleregulatory CDK inhibitors [4,13]. EZH2 depletion in T lymphocytes disrupts genomic transcriptome and gene bivalent states [14], rendering loss-of-defense to pathogens [15], autoimmune diseases [15][16][17], or cell death via apoptosis [12].…”
Section: Physiological Function Of Ezh2 In Lymphogenesis Ezh2 In T Cellsmentioning
confidence: 99%
“…Modulatory functions of EZH2 have been investigated intensively in several different subtypes and developmental phases of T lymphocyte, including T helper, T regulatory, cytotoxic T, memory T, natural killer (NK) T, and naïve T cells. Detailed findings of how EZH2 deploys H3K27 tri-methylation to regulate T cell development are summarized in Table 1 [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Physiological Function Of Ezh2 In Lymphogenesis Ezh2 In T Cellsmentioning
confidence: 99%
“…UTX (ubiquitously transcribed tetratricopeptide repeat, X chromosome; KDM6A)mediated H3K27me3 demethylation enforces Tfh-related gene expression such as IL6ra to sustain Tfh lineage, and deficiency in UTX leads to impaired GC B cell response and antibody production against chronic virus infection (Cook et al, 2015). In addition, the H3K27me3 methyltransferase Ezh2 is required for Tfh generation (Chen et al, 2019;Li et al, 2018). H3K36 methylation is another important histone modification and has gained attention in recent years (Wagner and Carpenter, 2012).…”
Section: Introductionmentioning
confidence: 99%